Customer development of effective performance indicators in local and state level public administration - Schulz, Rebekah; Sense, Andrew; Pepper, Matthew J., 1977- (Emerald Publishing Limited, 2021)
As communities demand more transparency and involvement in community affairs, local public administrators and government authorities are seeking new ways to meet those needs. A fundamental way to bridge community needs with authority's actions is through the customer-oriented development of Performance Indicators (PI). However, this is often not a core focal point and as a result, performance indicators are often output and not impact focused, and thus can lack relevance and utility. Addressing this gap in academic and practical knowledge, 'Customer Development of Effective Performance Indicators in Local and State Level Public Administration' presents a structured process to enable public organisations and their communities to jointly develop performance indicators for public organisation's operations, and enabling communities to determine key performance indicators that are both highly relevant and contextually useful. Grounded in quality management principles, the book encourages community members to participate in practical co-production, promotes mutual learning and joint ownership, fosters relationship building between diverse customer groups, and inspires open conversations regarding local government operations. This book provides ground breaking insights for public administrators at all levels, as well community leaders, and scholars of business, public administration, and social responsibility.